2018
DOI: 10.5694/mja18.00646
|View full text |Cite
|
Sign up to set email alerts
|

National Heart Foundation of Australia and Cardiac Society of Australia and New Zealand: Australian clinical guidelines for the diagnosis and management of atrial fibrillation 2018

Abstract: Introduction: Atrial fibrillation (AF) is increasing in prevalence and is associated with significant morbidity and mortality. The optimal diagnostic and treatment strategies for AF are continually evolving and care for patients requires confidence in integrating these new developments into practice. These clinical practice guidelines will assist Australian practitioners in the diagnosis and management of adult patients with AF. Main recommendations: These guidelines provide advice on the standardised assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
116
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 55 publications
(77 reference statements)
1
116
1
Order By: Relevance
“…In summary, the higher risk for ischemic stroke in women than in men seems to be lower than reflected by the The aim of our study was to evaluate the risk for stroke and death in women and men, but not to revise the CHA 2 DS 2 -VASc risk score, for example, without sex category as has been suggested in some recent publications. 11,19 As already pointed out, all CHA 2 DS 2 -VASc This study has limitations. It was observational and should thereby be interpreted with caution, despite careful selection of diagnosis codes for estimation of the CHA 2 DS 2 -VASc score, the selection of robust outcomes of ischemic stroke and death, and the extensive statistical analyses.…”
Section: Discussionmentioning
confidence: 82%
“…In summary, the higher risk for ischemic stroke in women than in men seems to be lower than reflected by the The aim of our study was to evaluate the risk for stroke and death in women and men, but not to revise the CHA 2 DS 2 -VASc risk score, for example, without sex category as has been suggested in some recent publications. 11,19 As already pointed out, all CHA 2 DS 2 -VASc This study has limitations. It was observational and should thereby be interpreted with caution, despite careful selection of diagnosis codes for estimation of the CHA 2 DS 2 -VASc score, the selection of robust outcomes of ischemic stroke and death, and the extensive statistical analyses.…”
Section: Discussionmentioning
confidence: 82%
“…19 Additionally, The Australian Clinical Guidelines for the Diagnosis and Management of Atrial Fibrillation suggested using different doses or agents other than high-dose dabigatran or rivaroxaban in patients with prior GIT bleeding. 10 The American College of Chest Physician guidelines refer to the indirect comparisons between NOACs in VTE management, favoring apixaban due to the lower risk of bleeding. 20 Standard treatment for IDA includes blood transfusion and iron replacement either orally, as first-line therapy, or intravenously for more profound IDA or in elderly patients.…”
Section: Discussionmentioning
confidence: 62%
“…9 Apixaban has the most favorable GIT bleeding risk profile and is recently recommended as the NOAC of choice in high-risk GIT bleeding patients by the Australian atrial fibrillation management guidelines. 10 Iron deficiency anemia (IDA) in developed countries is usually related to overt or covert GIT blood loss. 11 There is limited research investigating the association between the use of NOACs and IDA in the absence of major GIT bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) It is also used to reduce the incidence of hospitalization in HF patients with reduced ejection fraction, 3) as well as to maintain the heart rate in patients with atrial fibrillation. 4) However, emergency visits and hospitalization due to adverse reactions to digoxin occur frequently, 5,6) since it has a very narrow therapeutic range. 7) In addition, a higher serum digoxin concentration (SDC, ≥1.2 ng/mL) appears to increase the risk of hospitalization or all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…9) The package insert of digoxin and guidelines recommend TDM for digoxin. 3,4,10) Studies from Japan and the United States (US) indicated that TDM was performed in 17−50% of patients receiving digoxin. 7,11,12) However, there is not much information in the literature regarding the frequency of TDM for digoxin.…”
Section: Introductionmentioning
confidence: 99%